P63-expressing Prostate Adenocarcinoma: A Case Study of a Rare Subtype. (9th November 2022) - Harbert, J; Chen, J; Dewenter, T; Bhalla, R; Halat, S K
Abstract: Introduction/Objective: Prostate acinar adenocarcinoma (PCa) is a well-researched, and often diagnosed entity. A combination of architectural and cytologic characteristics are used in accurately identifying these carcinomas. However, the diagnosis can be challenging when the foci are minute or the cancer presents with unusual features. Ancillary studies aid in these scenarios. The loss of basal cells in adenocarcinoma makes markers targeting these cells desirable. PIN4 cocktail immunohistochemical stain, which combines alpha-methylacyl-coA racemase (AMACR), that is overexpressed in prostate carcinoma, with basal markers high molecular weight cytokeratin and p63, is a popular ancillary study to assist diagnosing demanding cases. Herein, we present a rare, challenging subtype of prostate carcinoma expressing p63. Methods/Case Report: A 66-year-old male, with a past medical history of treated HIV and hyperlipidemia, underwent screening biopsies for a PSA of 7.5 ng/mL. Out of 22 parts, three cores showed modest amounts of atypical infiltrating cells. The architecture comprised of ill-defined glands, individual cells and single files of cells. They possessed high nucleocytoplasmic ratio giving a hint of atrophy, with occasional spindling and prominent nucleoli. To add to the challenge, PIN4 immunostaining showed strong nuclear expression of a basal marker with negative AMACR. Due to unusual morphology and basal marker expression, a consideration of basal cell lesion was entertained. However, subsequent staining revealed negative expression of HMWCK, and positive expressions of NKX3.1 and p40. Overall, with this morphology and immunoprofile we diagnosed our case as prostate carcinoma with aberrant expression of p63. Results (if a Case Study enter NA): N/A Conclusion: Grading these lesions is controversial as they are considered to carry a better prognosis over conventional acinar adenocarcinoma of similar grade. A distinct etiopathology is suspected as molecular tests for ERG and PTEN are without alterations. Further discussion and characterization of these lesions is warranted as they are infrequently encountered and prone to being overlooked due to their similarities to benign basal cells.